High-index planes T-Nb2O5 using self-assembly strategy for aerobic oxidative desulfurization in fuels. (1st January 2022) - Yu, Zhendong; Lü, Xinhua; Xun, Suhang; He, Minqiang; Zhu, Linhua; Chen, Haofeng; Yuan, Mengmeng; Fan, Lei; Zhu, Wenshuai
Graphical abstract: T-Nb2 O5 using solvent evaporation-induced self-assembly strategy for molecular oxygen oxidation of aromatic sulfides. Highlights: Nb2 O5 materials is first applied for the aerobic ODS using self-assembly strategy. Molecular oxygen is activated under mild conditions with Nb2 O5  catalysts. The mechanism of DBT oxidation is proposed with O2 –  formation. Abstract: High-index planes viewed as reactive facets are possessed of the high-density, low-coordination atoms, which are distributed at catalytic sites with high activity, such as steps, edges and kink sites. Herein, the orthorhombic niobium pentoxide (T-Nb2 O5 ) is synthesized, with the elevated ratio of high-index planes, first for aerobic oxidative desulfurization (ODS) of the refractory aromatic sulfides. Through a solvent evaporation-induced self-assembly strategy, mesoporous structure Nb2 O5 with three different crystal phases, amorphous, pseudo-hexagonal and orthorhombic, are prepared using the calcination method. The proportion of high-index facets increases, as raising the calcination temperature, which contributes to the faster production of the superoxide free radical (O2 – ) intermediate using molecular oxygen as the green oxidant. Under optimal conditions, a 100% sulfur removal rate is obtained using 650 °C-T-Nb2 O5 within 7 h, showing its excellent catalytic performance. The cycle experiments confirm the stability of the prepared 650 °C-T-Nb2 O5 after 8 times regeneration process, showing a promising prospect of NbO x -based materials for ODS under mild conditions.